2019
DOI: 10.1515/dmpt-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Association of IRS1 genetic variants with glucose control and insulin resistance in type 2 diabetic patients from Bosnia and Herzegovina

Abstract: Background Previous studies reported conflicting results regarding association of insulin receptor substrate 1 (IRS1) gene variation with type 2 diabetes (T2D) and insulin resistance (IR) in different ethnic groups. We examined the association of rs7578326, rs2943641, and rs4675095 in the IRS1 gene with T2D and related traits in a population from Bosnia and Herzegovina, which is one of the European countries with the highest T2D prevalence of 12.5%. Methods Our study included 390 T2D patients and 252 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…INS sensitivity can be improved by 4-PBA through reversing ER stress in adipose tissue 61. It has been shown that IRS-mediated INS receptor signaling dysregulation is a common underlying mechanism that can produce and exacerbate INS resistance in many genetic and physiological factors 62,63. INS signaling in adipocytes is critical for the development of obesity 64.…”
Section: Discussionmentioning
confidence: 99%
“…INS sensitivity can be improved by 4-PBA through reversing ER stress in adipose tissue 61. It has been shown that IRS-mediated INS receptor signaling dysregulation is a common underlying mechanism that can produce and exacerbate INS resistance in many genetic and physiological factors 62,63. INS signaling in adipocytes is critical for the development of obesity 64.…”
Section: Discussionmentioning
confidence: 99%
“…The individuals with non-insulin dependent diabetes mellitus (NIDDM) have decreased expression and function of IRS-1 in the fat cells. The Gly972Arg polymorphism is the most commonly studied variant of IRS-1 [12]. Downstream IRS-1, the main docking protein found in the cells is IRS-2 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mutation or abnormal expression of IRS1 is mainly related to type II diabetes, insulin resistance, cognitive dysfunction and tumor. 61 , 62 , 63 , 64 Kapogiannis et al. measured human plasma exosomes, and the results showed that IRS1 (p-Ser312) and its tyrosine phosphorylation in AD group were significantly different from other groups.…”
Section: Discussionmentioning
confidence: 99%